2018
DOI: 10.1038/s41598-018-31034-z
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of β-Adrenoceptor Signaling in Left Ventricle of Acute Phase Takotsubo Syndrome: a Human Study

Abstract: Accumulating evidence indicates alteration of the β-adrenoceptor (AR), such as desensitization and subtype switching of its coupling G protein, plays a role in the protection against catecholamine toxicity in heart failure. However, in human takotsubo syndrome (TTS), which is associated with a surge of circulating catecholamine in the acute phase, there is no histologic evidence of β-AR alteration. The purpose of this study was to investigate the involvement of alteration of β-AR signaling in the mechanism of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 40 publications
2
35
0
1
Order By: Relevance
“…The exposure of myocardium to large concentrations of circulating catecholamines during LT makes the heart susceptible to adverse events including multivessel epicardial vasospasm [71]. In addition, the altered adrenergic and Gs protein signaling pathways that are commonly found in heart tissue of cirrhotic patients have been suggested to contribute in TTC physiology [72].…”
Section: Pathophysiologymentioning
confidence: 99%
“…The exposure of myocardium to large concentrations of circulating catecholamines during LT makes the heart susceptible to adverse events including multivessel epicardial vasospasm [71]. In addition, the altered adrenergic and Gs protein signaling pathways that are commonly found in heart tissue of cirrhotic patients have been suggested to contribute in TTC physiology [72].…”
Section: Pathophysiologymentioning
confidence: 99%
“…Location and the extent of wall motion abnormalities in TTS may be explained by the distribution of the β2-AR [ 18 ]. More recently, we demonstrated in vivo evidence of β-AR alteration [ 19 ]. Left ventricular biopsy samples from patients with TTS demonstrated more abundantly expressed G protein coupled receptor kinase 2 (GRK2) and β-arrestin2, both of which are known to desensitize β-AR, than in samples from dilated cardiomyopathy.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, L41Q polymorphism of GRK5, one of the two isoforms predominant in the heart, makes patients susceptible to TTS . An interesting study showed that GRK2 and β‐arrestin 2 expression in the myocardium was higher in TTS than in dilated cardiomyopathy or controls in the acute phase, supporting the concept that β‐adrenergic receptors on the cell membrane are modified by GRK2 and β‐arrestin 2, confirming their role in the development of LV dysfunction in TTS …”
Section: Introductionmentioning
confidence: 87%